Phonemic Inventory in Lungkhim - Rai, Tara Mani (Nepalese Linguistics, 2022)
This article attempts to explore the phonemes embedded to the Lungkhim. There are altogether 29 phonemes in Lungkhim. Of them, there are 6 vowels and 23 consonants. Consonants show four-way contrasts or oppositions: place of articulation, manner of articulation, voicing and aspiration.